The Description Of Hemoglobin Levels In Pregnant Woman In Work Area Of Puskesmas Tampaksiring I - Made Ariastuti Prabandari Putri; Nur Habibah; I Gusti Agung Ayu Putu Swastini (Meditory : The Journal of Medical Laboratory, 2022)
Background Anemia in pregnancy is a major health problem in developing countries with a high level of morbidity in pregnant women. The incidence of anemia in pregnancy is a condition of pregnant women with hemoglobin (Hb) levels 11 g/dL in the first and third trimesters, meanwhile in the second trimester Hb levels 10.5 g/dL. The purpose of this study was to determine the description of hemoglobin levels in pregnant women in the work area of Puskesmas Tampaksiring I. The research method used a descriptive type of research conducted in January-May 2022 with a total of 38 respondents obtained by random sampling technique. Hemoglobin levels were measured by the Point Of Care Testing (POCT) method. The results showed that 38 respondents (42.1%) had low hemoglobin levels, (55.3%) had normal hemoglobin levels, and (2.6%) had high hemoglobin levels. Low hemoglobin levels were mostly found in pregnant women who were in the range of 18-25 years, with less knowledge and were in a risky gestational age (Trimester I and III) and did not comply in taking blood-boosting tablets (TTD). The conclusion of this study is that most pregnant women have normal hemoglobin levels with a percentage of 55.3%.